Análisis geotécnico de los tipos de materiales existentes en varios puntos del sector Pascuales en Guayaquil - Conforme Bulgarin, Roberto Antonio (2024)
In the Pascuales sector, a significant problem was detected in the streets due to the presence of cracks and fissures in the soil, which led to the need for an exhaustive geotechnical analysis. To evaluate the condition of the soil, soil pits were dug at various points in the sector, and five samples were extracted and subjected to various laboratory tests to determine their properties and characteristics. The research was carried out using a descriptive and experimental approach, providing a comprehensive view of the condition of the soil in Pascuales. The results of the tests revealed deficiencies in soil quality, which led to the formulation of specific recommendations to ensure compliance with current regulations. In addition, a TPDA (Traffic Daily Average Annual) was conducted to determine the most optimal pavement design for the road. After the analysis, it was concluded that the rigid design was the most suitable for the Pascuales sector. The recommendations not only seek to improve the stability and durability of future constructions, but also to provide the scientific community with relevant information for future research in the field of geotechnical engineering. Furthermore, these proposed measures have the potential to significantly improve the road infrastructure of the sector, contributing to a safer and more sustainable urban development.